1986
DOI: 10.1152/ajprenal.1986.251.5.f765
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species: production and role in the kidney

Abstract: Reactive oxygen species (ROS) are formed by incomplete reduction of molecular oxygen. They include superoxide anion (O2-.), hydrogen peroxide (H2O2), hydroxyl radical (OH.), and singlet oxygen (1O2). ROS may induce different types of cell injury, particularly lipid peroxidation and membrane damage. ROS have been shown to play an essential role in the mechanisms of experimental models of several renal diseases: ischemic acute renal failure, renal graft rejection, acute glomerulonephritis, and toxic renal diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
137
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(141 citation statements)
references
References 0 publications
2
137
0
2
Order By: Relevance
“…The kidney is susceptible to oxidative damage induced by ischemia-reperfusion, inflammatory, and toxic drug reactions that can lead to renal diseases such as acute ischemic renal failure, acute glomerulonephritis, and chronic or acute tubular disease (9). Although circulating leukocytes are known to be important mediators of oxidative damage to renal tissues, particularly the glomerular basement membrane, several resident renal cell types are also recognized for their capacity for significant superoxide release.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The kidney is susceptible to oxidative damage induced by ischemia-reperfusion, inflammatory, and toxic drug reactions that can lead to renal diseases such as acute ischemic renal failure, acute glomerulonephritis, and chronic or acute tubular disease (9). Although circulating leukocytes are known to be important mediators of oxidative damage to renal tissues, particularly the glomerular basement membrane, several resident renal cell types are also recognized for their capacity for significant superoxide release.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-free assays have also detected NADH and NADPH-dependent oxidase activities in tubular cell membrane preparations (25), although the identities of these enzymes have been unclear. The identification of Renox as a source of superoxide in proximal convoluted tubules could have important physiological and pathological implications, because ROS play significant roles in tubular hypertrophic responses to angiotensin II (26) and the nephrotoxicity of drugs such as cyclosporin and aminoglycosides (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated that reactive oxygen species play an important role in ischemic acute renal failure, [3][4][5][6] . Several in vivo animal studies document a role of reactive oxygen molecules in causing tissue injury [7][8][9][10] Ascorbic acid has been used to protect against corneal damage from free radicals in rabbits 11 . In addition, it has also been used to improve the renal hemodynamics and decrease oxidative stress, inflammation and fibrosis in the ischemic kidney of pigs 12 .…”
Section: Introductionmentioning
confidence: 99%
“…A profound imbalance between oxidants and antioxidants has been related to renal disorders, from minimal change nephritic syndrome to obstructive nephropathy (16,18). Moreover, patients with end-stage renal failure on maintenance hemodialysis are chronically exposed to the oxidative stress generated by reactive oxygen species due to perdialytic neutrophil activation (19).…”
mentioning
confidence: 99%